NAD+-mediated SIRT1–LKB1–AMPK signaling drives lipid remodeling and meat quality differences between Daweishan miniature and Arbor Acres chicken breeds - Wu, Hao; Luo, Junfeng; Jian, Zonghui; Yang, Min; Zhao, Jingying; Fu, Jing; Yan, Shixiong; Dou, Tengfei; Jia, Junjing; Liu, Lixian; Xu, Zhiqiang (Frontiers in Veterinary Science, 2025)
IntroductionThis study aimed to compare the meat composition, nicotinamide adenine dinucleotide (NAD+) metabolism, SIRT1–LKB1–AMPK signaling, and lipid profiles between the slow-growing Daweishan miniature (M1) and fast-growing Arbor Acres (A1) broiler breeds. Methods: Breast muscle samples were collected at 30 days of age (n = 6/breed) for chemical analysis, targeted metabolomics, ELISA, and LC–MS-based lipidomics.ResultsChemical composition showed higher moisture and fat contents in A1 broilers, whereas M1 chickens had greater protein contents (p < 0.05). The concentrations of NAD+ and its key precursors, including nicotinamide (NAM), nicotinamide mononucleotide (NMN), and nicotinamide riboside (NR), were higher (p < 0.05) in the M1 as compared to the A1 chicken breed. ELISA results showed an increased concentration of SIRT1, LKB1, and AMPK in M1 chickens, which was positively associated with NAD+ and its precursors. Lipidomics identified 1,772 lipids across 69 subclasses, with 378 and 310 differentially expressed molecules. The M1 chickens showed downregulation of triglycerides and cholesteryl esters, with mixed regulation of fatty acids. Correlation analysis suggested that NAD+-driven SIRT1–LKB1–AMPK signaling associated with lipid catabolism, inhibits lipogenesis, and remodels fatty acid composition.ConclusionThese results indicate that M1 chickens exhibit enhanced metabolic regulation and protein-rich muscle with distinct lipid remodeling, whereas A1 broilers favor rapid growth and fat accumulation. The study provides mechanistic insight into breed-specific differences in muscle metabolism and meat quality, highlighting NAD+ and its signaling axis as key regulators of lipid homeostasis in chicken breast muscle.